An empirical study of peer feedback in translation didactics: quality, response and student perceptions. Issue 8 (14th November 2022) - Li, Xiaosa; Ke, Ping
Abstract: This study investigates the implementation of peer feedback in an advanced English-Chinese translation course. Teacher scaffolding was provided to 20 students who completed two translation-feedback-revision cycles. A survey was then administered to the class, followed by a semi-structured interview with six students. The study yielded rather positive results, with the overall accuracy rate of peer feedback comments and the incorporation rate surpassing 75% in both tasks; students were generally positive about the peer feedback processes; doing peer feedback triggered reflective comparisons and internal feedback mechanisms. The findings provide empirical evidence that peer feedback not only has great potential to enhance student performance, but can also help to promote subsequent action upon feedback, facilitate engagement with translation criteria, and foster the ability to make evaluative judgments.